1997
DOI: 10.1089/acm.1997.3.241
|View full text |Cite
|
Sign up to set email alerts
|

A Double Blind, Randomized, Controlled Investigation of Electrodermal Testing in the Diagnosis of Allergies

Abstract: This investigation evaluates electrodermal (ED) testing in 41 polysymptomatic allergic patients. Electrodermal testing discriminated correctly 82% of the time between house dust mite and histamine (allergens) and saline or water (nonallergens) in our first study group involving 17 patients (p = 0.007). The second study involved 24 patients and used the same double-blind methodology discriminating 96% of the time between allergic and nonallergic substances (p = 0.000002). We conclude that ED testing is a reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…[15][16][17] All three studies used the VEGA test method developed by Schimmel 20 as an adaptation of EAV. A brief description of VEGA testing is provided by Tsuei 8 and Jeremic and Leung.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[15][16][17] All three studies used the VEGA test method developed by Schimmel 20 as an adaptation of EAV. A brief description of VEGA testing is provided by Tsuei 8 and Jeremic and Leung.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study, the least rigorous of the three, 15 reported correct patient discrimination of allergens from non-allergens in 82% of the fi rst group and 96% of the second group of subjects tested. Their measure of discrimination was the percentage of subjects who showed a positive response to mites or histamine as distinct from distilled water or saline.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations